Does Equity Market Integration Exist Between Turkey and the Eurozone? - Usman, Berto; Kassie, Nega Muhabaw; Wahyudi, Fitra (Universitas Negeri Semarang, 2018)
This research investigates the existence of stock market integration between Turkey and the Eurozone. In this study, the performance of Turkey’s stock exchange is proxied by the BIST100, and the EURO STOXX50 is employed as a proxy for the Eurozone index. We hypothesize that there is a dynamic relationship between Turkey and the Eurozone. Methodologically, our research was conducted by employing monthly time series data obtained from EIKON datastream International. In order to demonstrate the extent of equity market integration between Turkey and Eurozone, a vector autoregression model (VAR) was utilized. According to the results, there is no co-integration between these two equity markets. This is in line with the output of residual matrix test, where the correlation between these two market indices was found to be low. However, a Granger causality test indicated that there was a low one-way contribution from Turkey to the Eurozone index during the observation period.